Antennas for radar and communications a polarimatric approach - Mott, Harold (Wiley series in microwave and optical engineering, 1992)
Introduces antenna theory, covering all the topics necessary for antennas used in radar and communications. Important areas treated include antenna noise, matching of misaligned antennas and radiation of a quasimonochromatic wave by an antenna. Further discussions explore wave polarization and target detection. Appendices include the Mueller and Kennaugh Matrices